2006
DOI: 10.1159/000093756
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status as a Risk Factor in Esophageal Surgery

Abstract: Background: Nutritional condition is one of the factors determining postoperative outcome in esophageal surgery. This study explored the relation between preoperative nutritional status and postoperative infectious complications. Methods: From a prospective database, 400 patients who underwent esophageal resection for malignancy were selected. Preoperative nutritional status was assessed by body mass index, prognostic nutritional index (PNI), nutritional risk index (NRI) and weight loss. The association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…These results are in accordance with later studies, indicating that nutritional status preoperatively, expressed as PNI, was significantly related with the occurrence of severe complications and was a predictive factor for long-term survival [25,26]. Nevertheless, Han-Geurts et al showed that PNI was not associated with postoperative infectious complications in patients who underwent esophageal resection for malignancy [27]. NRS-2002 is recommended by the European Society for Clinical Nutrition and Metabolism as a standard tool for the assessment of surgical patients [28], but it is not tailored to esophageal cancer patients, thus limiting its prognostic value in this population.…”
Section: Methods Of Nutritional Assessment and Impact On Clinical Outsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in accordance with later studies, indicating that nutritional status preoperatively, expressed as PNI, was significantly related with the occurrence of severe complications and was a predictive factor for long-term survival [25,26]. Nevertheless, Han-Geurts et al showed that PNI was not associated with postoperative infectious complications in patients who underwent esophageal resection for malignancy [27]. NRS-2002 is recommended by the European Society for Clinical Nutrition and Metabolism as a standard tool for the assessment of surgical patients [28], but it is not tailored to esophageal cancer patients, thus limiting its prognostic value in this population.…”
Section: Methods Of Nutritional Assessment and Impact On Clinical Outsupporting
confidence: 89%
“…NRI is another tool used for the assessment of malnutrition based on serum albumin concentration and weight loss. Ιncreased nutritional risk, derived from NRI, is associated with reduced survival in esophageal cancer patients treated with definitive chemoradiotherapy [10,33], but is not associated with postoperative infectious complications in patients treated with esophagectomy [27]. The Geriatric Nutritional Risk Index (GNRI) is a new index recently introduced for the assessment of nutritional status of elderly patients.…”
Section: Methods Of Nutritional Assessment and Impact On Clinical Outmentioning
confidence: 99%
“…The relationship between the preoperative nutritional status and the outcome of surgery in patients with oesophageal carcinoma has shown conflicting results [58][59][60][61] . In one study, underweight patients who underwent major intra-abdominal surgery, e.g., oesophagectomy, had a five-fold increased risk of postoperative mortality 59 .…”
Section: Patient Selectionmentioning
confidence: 99%
“…Though, other studies including exclusively oesophageal cancer patients have not confirmed this 58;60 . In four studies, complication rates for obese patients equalled those for non-obese patients [58][59][60][61] .…”
Section: Patient Selectionmentioning
confidence: 99%
“…Nutritional status is a predictive factor in post-operative outcomes (2) . Neo-adjuvant chemotherapy followed by surgery is the treatment of choice for the majority of these patients (3) .…”
mentioning
confidence: 99%